rdlc 2022
DOI: 10.7764/rdlc.21.2.427
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on behavior and seismic performance of reduced beam sections

Abstract: Engineers prefer reduced beam section (RBS) connections in steel moment frames built in earthquake zones due to their many benefits. The RBS shape design significantly affects joint behavior. This paper examines the effect of RBS geometry on joint behavior and seismic performance using ANSYS finite element analysis software. RBS connections are investigated using European profiles and steel grades due to the limited number of studies using European profiles in the literature. The simulation study is carried ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Artificial intelligence-based models are increasingly being employed widely in almost every single field with developing technology. For example, it has been demonstrated that there are important contributions in modeling the steel connections of seismic performance used in civil engineering with artificial intelligence [29][30][31]. As another example, Guerra et al [32] performed a comparative study of swarm intelligence metaheuristics in the unscented Kalman filter-based neural training applied to the identification and control of robotic manipulators.…”
Section: Modelmentioning
confidence: 99%
“…Artificial intelligence-based models are increasingly being employed widely in almost every single field with developing technology. For example, it has been demonstrated that there are important contributions in modeling the steel connections of seismic performance used in civil engineering with artificial intelligence [29][30][31]. As another example, Guerra et al [32] performed a comparative study of swarm intelligence metaheuristics in the unscented Kalman filter-based neural training applied to the identification and control of robotic manipulators.…”
Section: Modelmentioning
confidence: 99%